Eugenol exposure in vitro inhibits the expressions of T3SS and TIF virulence genes in Salmonella Typhimurium and reduces its pathogenicity to chickens. (January 2022) - Zhao, Xin; Wei, SiMin; Tian, QiMing; Peng, WeiLong; Tao, Ya; Bo, RuoNan; Liu, MingJiang; Li, JinGui
Abstract: Background: Salmonella enterica serovar Typhimurium ( S. Typhimurium ) is a common food-borne pathogen, which has the ability to infect a wide range of hosts. The increasing emergence of drug-resistant strains urgently requires new alternative therapies. Eugenol has been shown to be very effective against drug-resistant strains of Gram-negative and Gram-positive bacteria. The purpose of this study is to explore the effects of eugenol on the virulence factors and pathogenicity of S. Typhimurium . Methods: The antibacterial activity of eugenol was investigated via the changes of cell morphology, fimbriae related-genes and virulence factors of S. Typhimurium, then the pathogenicity of S. Typhimurium pretreated by eugenol to chickens was evaluated. Results: Susceptibility testing showed that eugenol possessed significant antimicrobial activity. Scanning electron microscope analysis showed eugenol treatment deformed the morphology with damaged fimbriae structure of S. Typhimurium . Real time PCR assay confirmed eugenol significantly down-regulated the expressions of virulence factors ( hilA, hilD, sipA, sipC, spiC, misL ) of Type III secretion system (T3SS) and adherence genes ( fimA, fimH, fimD, fimY, fimZ, stm0551 ) of Type I fimbriae (TIF). Animal experiment proved that the pathogenicity of S. Typhimurium exposed by eugenol was reduced, which was evidenced by the higher survival rate, weight gains and organs indexes, the lower bacterial loads in organs. Meanwhile, the duodenal histopathological changes were mitigated, with a significantly decline in the expressions of TNF-α, IL-6 and IL-18. Conclusion: In summary, eugenol pretreatment may alleviate the pathogenicity of the S. Typhimurium to chickens via wrecking the fimbriae and inhibiting the mRNA expressions of virulence factors and adhesion molecules. These data dedicated the potential mechanisms of eugenol against S. Typhimurium in vitro. Highlights: Sub-MIC eugenol reduced fimbria formation with bacterial deformation and declined adherence genes of TIF. Sub-MIC eugenol significantly inhibited virulence genes expression of T3SS. Sub-MIC eugenol weakened the pathogenicity of S. Typhi to chickens.